Oral History Interview with Howard Hunter: Conceptualising SMU - HUNTER, Howard (Institutional Knowledge at Singapore Management University, 2011)
The interview covered: first involvement with SMU, roles and responsibilities, tuition fees, autonomous university, law school, Juris Doctor program, undergraduate education, marketing, SMU pedagogy, curriculum, university library, Biography: Professor of Law, SMU, 2004–presentPresident, SMU, 2004–2010 Described as a passionate educator who truly believes in multidisciplinary education, Professor Howard Hunter served as SMU’s third president from September 2004 to August 2010. During the course of his presidency the university continued its rapid growth—moving to the city campus, opening the law school, expanding postgraduate programmes, building the endowment, and doubling the number of students and faculty. While at SMU he emphasized experiential learning through internships and community service. After stepping down from the presidency, Professor Hunter continues to teach as a member of SMU’s law faculty; his areas of specialisation are contract and commercial law, and American constitutional law. Professor Howard Hunter practised law in the United States before joining the Emory University law school faculty in 1976. During his twenty-eight years at Emory he served as dean of Emory Law School and interim provost of Emory University. He has been a visiting professor of law at the University of Virginia and the College of William & Mary in the US, the University of Hong Kong, and a Fulbright Senior Scholar at the University of Sydney law school in Australia. From 1991 to 1997 he was co-director of the American Law Centre in Moscow. He has lectured at numerous conferences in Asia, Europe, and North America. Currently, he is a recurring visiting professor of law at the Central European University in Budapest, Hungary. Professor Hunter is the author of Modern Law of Contracts. He has published articles on contract law, the first amendment, and academic freedom. He is a member of the board of editors of the Journal of Contract Law. Professor Hunter is a member of the State Bar of Georgia, the New York State Bar Association, and the American Bar Association. He is an associate member of the Law Society of Singapore and a life member of the American Law Institute. He received the Amicus Curiae award from the Supreme Court of Georgia in 1998 for his service to the profession. He served on the Chief Justice's Commission on Professionalism (1990–2004) and the Georgia Supreme Court Commission on Indigent Defence (2000–2004). He was appointed a board member of the American Arbitration Association in May 2006. An active member of Singapore’s business community, Professor Hunter has served on numerous boards in Singapore, such as, the Competition Appeal Board, the Singapore International Chamber of Commerce, the American Chamber of Commerce of Singapore, and the Singapore National Research Foundation. He received his undergraduate and legal education at Yale University (USA), and was admitted to the bar in 1971.